Incidence of postoperative nausea and vomiting in patients at a university hospital. Where are we today? - Doubravská, Lenka; Dostálová, Kateřina; Fritscherová, Šárka; Zapletalová, Jana; Adamus, Milan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2010)
AIM: To determine the incidence of postoperative nausea and vomiting (PONV), identify risk factors, assess treatment and its effectiveness. DESIGN: A prospective, observational, questionnaire- and interview-based study. SETTING: Standard and intensive care units of the following university hospital departments: abdominal, thoracic and vascular surgery; gynecology; plastic and esthetic surgery; urology; and traumatology. MATERIAL AND METHODS: Adult patients scheduled for elective surgery who gave informed consent were enrolled. A questionnaire-based study was performed on the first postoperative day. The collected data relevant to PONV were statistically analyzed. CONCLUSION: The incidence of PONV was significantly lower than generally presumed and was related to the patient gender, type of surgery and overall health status. PONV was more frequent in obese patients and when drugs antagonizing opioids or muscle relaxants were used. Early administration of antiemetic agents led to considerably less discomfort.
Keywords: financování organizované; dospělí; Female; Hospitals, University; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Postoperative Nausea and Vomiting; Aged, 80 and over; Financing, Organized; Risk Factors; Incidence; Male; incidence; Aged; Young Adult; rizikové faktory; lidé středního věku; nemocnice univerzitní; senioři nad 80 let; senioři; mužské pohlaví; pooperační nevolnost a zvracení; Middle Aged; mladiství; Humans